Fluid provision and metabolic responses to soccer-specific exercise - Clarke, N. D.; Drust, B.; Maclaren, D. P. M.; Reilly, T. (European Journal of Applied Physiology, 2008)
The present study aimed to investigate the impact on metabolism of altering the timing and volume of ingested carbohydrate during soccer-specific exercise. Twelve soccer players performed a soccer-specific protocol on three occasions. On two, 7 ml/kg carbohydrate-electrolyte or placebo were ingested at 0 and 45 min. On a third, the same total volume of carbohydrate-electrolyte was consumed but at 0, 15, 30, 45, 60 and 75 min. Carbohydrate-electrolyte ingestion increased blood glucose, insulin and carbohydrate oxidation, whilst suppressing NEFA, glycerol and fat oxidation (P < 0.05) although manipulating the schedule of carbohydrate ingestion elicited similar metabolic responses (P > 0.05). However, consuming fluid in small volumes reduced the sensation of gut fullness (P < 0.05). The results demonstrated that when the total volume of carbohydrate consumed is equal, manipulating the timing and volume of ingestion elicits similar metabolic responses. Furthermore, consuming a small volume of fluid at regular intervals reduces the sensation of gut fullness.